2017
DOI: 10.22159/ijpps.2017v9i3.16579
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Fusarium Oxysporum in Unsterilized Soil by Novel Streptomyces Cacaoi Subsp Cacaoi [M20]

Abstract: Objective: To find bio fungicide from mangrove actinomycetes for controlling seed and soil borne pathogen-Fusarium oxysporum.Methods: A total of 25 actinomycetes were isolated by pour plate method. These were screened for fungicidal activity by agar plug method. The isolate M20 was characterised further for identification. The phytotoxicity study was done; biocontrol of Fusarium oxysporum with 10% culture filtrate was done using food poisoning technique. Volatile toxicity of isolate M20 was studied by inverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… Have an antifungal activity such as Burkholderia rinojensis, Burkholderia seminalis TC3.4.2R3, Burkholderia cepacia , Burkholderia gladioli , Burkholderia cenocepacia, Burkholderia ambifaria able to degrade fusaric acid ( Abdel-aziz et al., 2020 ); ( Diana et al., 2017 ); ( Heydari and Misaghi, 1998 ); ( Li et al., 2007 ); ( Elshafie et al., 2012 ); ( Rojas-rojas et al., 2018 ); ( Simonetti et al., 2018 ) Streptomyces kanamycetius Producing kanamycin ( Basak and Majumdar, 1975 ). Streptomyces rishiriensis Producing coumermycin ( Li et al., 2002 ) Streptomyces cacaoi As an antifungal activity against Fusarium ( Janaki, 2017 ) Bacillus mycoides Inducing colonization of endophytic bacteria ( Yi et al., 2017 ) …”
Section: Resultsmentioning
confidence: 99%
“… Have an antifungal activity such as Burkholderia rinojensis, Burkholderia seminalis TC3.4.2R3, Burkholderia cepacia , Burkholderia gladioli , Burkholderia cenocepacia, Burkholderia ambifaria able to degrade fusaric acid ( Abdel-aziz et al., 2020 ); ( Diana et al., 2017 ); ( Heydari and Misaghi, 1998 ); ( Li et al., 2007 ); ( Elshafie et al., 2012 ); ( Rojas-rojas et al., 2018 ); ( Simonetti et al., 2018 ) Streptomyces kanamycetius Producing kanamycin ( Basak and Majumdar, 1975 ). Streptomyces rishiriensis Producing coumermycin ( Li et al., 2002 ) Streptomyces cacaoi As an antifungal activity against Fusarium ( Janaki, 2017 ) Bacillus mycoides Inducing colonization of endophytic bacteria ( Yi et al., 2017 ) …”
Section: Resultsmentioning
confidence: 99%
“…A work carried out by Sahoo et al, on PGPR (Bacillus amyloliquefaciens 937b and B. pumilus SE-34) showed protection against tomato mottle virus (TMV) [45]. Another study carried out on Streptomycetes cacaoi strain M-20 isolated from Avicennia marina rhizosphere has also shown antifungal activity against phytopathogen Fusarium oxysporum, which was reported to be responsible for the significant reduction in legume production [46]. Some studies had observed that the mycorrhizae bacteria provide resistance against fungal pathogens by inhibiting the growth of many root pathogens such as Rhizoctonia solani, Pythium spp., F. oxysporum, and Heterobasidion annosum (Fig.…”
Section: Beneficial Effect Of Rhizosphere Microbial Community On Plantmentioning
confidence: 99%
“…When the isolate M20 was tested for chitinase production, it was found better in the production of chitinase enzyme that may also responsible for cell wall degeneration in fungi. The study about chitinase production by Streptomyces sp got its support from the studies [25,26]. Molecular characterization of isolate M20 was done by 16S rRNA sequencing analysis.…”
Section: Biochemical and Molecular Characterization Of Isolate M20mentioning
confidence: 99%